How to predict progression-free survival in patients with grade 2 IDH-mutated diffuse gliomas after surgery: a long-term follow-up analysis - Aprile, Marta; Di Nunno, Vincenzo; Gatto, Lidia; Tosoni, Alicia; Balestrini, Damiano; Ramponi, Vania; Conti, Alfredo; Maffei, Monica; Battaglia, Stella; Argento, Chiara Maria; Zuliani, Enrico; Bartolini, Stefania; et al. (Frontiers in Oncology, 2025)
PurposeAvailable prognostic scores for adult-type diffuse glioma with isocitrate dehydrogenase (IDH) mutant were validated before the evaluation of biomolecular features. The selection of patients who did not receive postoperative radiotherapy and chemotherapy would provide an ideal setting to describe the natural history of these tumors.MethodsWe investigated the clinical outcomes of patients with adult-type diffuse glioma with isocitrate dehydrogenase IDH mutation approached with active surveillance after primary surgery.ResultsWe evaluated 61 patients consisting of 35 patients with IDH-mutant astrocytomas and 26 patients with IDH-mutant 1p19q oligodendrogliomas. The median follow-up was 13.1 years (95% CI 11.4–17.7). A total of 56 progression-free survival events were available at the time of analysis. The median age was 32.2 years, higher in IDH-mutant 1p19q oligodendrogliomas (39.5 years) compared to IDH-mutant astrocytomas (31.4 years; p = 0.003). Residual tumor [hazard ratio (HR) 2.63, 95% CI −1.23 to 5.58, p = 0.007], post-surgical diameter product (HR 1.11, 95% CI 1–1.22, p = 0.03), and midline crossing (HR 6.79, 95% CI 1.5–30.4, p = 0.005) were the only factors directly influencing progression-free survival in univariate analyses. No variables confirmed their predictive role in multivariate models. At the time of data analysis, we registered 22 overall survival (OS) events. In a multivariate Cox regression model, histo-molecular diagnosis (oligodendroglioma vs. astrocytoma; HR 0.28, 95% CI 0.10–0.8, p = 0.02) and initial tumor area assessed as continuous variables (HR 1.82, 95% CI 1.01–3.3, p = 0.05) independently affected the survival of patients (p = 0.01).ConclusionsIn our series, the presence and dimension of residual tumors and midline crossing were the only independent variables predicting progression-free survival after primary surgery in grade 2 diffuse glioma.